How urban green areas influence different dimensions of sustainable behaviour - Ferraz, Leonardo; Petroni, Liége Mariel; Santos, Emerson Gomes dos (Revista de Administração da UFSM, 2023)
Purpose: The alternative of sustainable consumption is proposed to change the excessive demand and production that aggravate environmental problems. However, translating ecosystems concerns into sustainable attitudes is a well-known challenge. This study analyzes the hypothesis of a positive correlation between how often people visit urban green areas and their perception of sustainable consumption Design/methodology/approach: Based on the nonparametric item response theory (NIRT) and logistic regression models. Findings: The hypothesis was partially confirmed. Implications: The importance of urban green areas and their potential to encourage sustainable consumption reinforces the need for governments to develop environmental education programs that include incentives to visit public parks and emphasize the reduction of environmental degradation. Originality/value: This research contributes (i) to present the importance of urban green areas to change the individuals’ behavior toward sustainable consumption and (ii) to test how urban green areas influence different dimensions of sustainable behavior.